2018
DOI: 10.1039/c8ra01365a
|View full text |Cite
|
Sign up to set email alerts
|

Sodium periodate/TEMPO as a selective and efficient system for amine oxidation

Abstract: NaIO4/TEMPO efficiently allowed a metal-free oxidation of benzylamines to benzaldehydes with complete selectivity for N-benzyl residues in secondary amines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“… 19 Very recently, Galletti et al reported NaIO 4 /TEMPO mediated conversion of benzylamines to carbonyls via imine formation and in situ hydrolysis using H 2 O/CH 3 CN as solvent. 20 However, these methods suffer from limitations such as higher temperature, long reaction time and sequence, substrate selectivity and extra step for imine hydrolysis to form an aldehyde. 17–20 In this context we envisioned that, PhI(OAc) 2 in combination with TEMPO used as an oxidizing agent to convert amine functional groups into corresponding carbonyl compounds at room temperature, with short reaction time and no use of external oxygen source (such as H 2 O or O 2 ) with excellent yields.…”
Section: Introductionmentioning
confidence: 99%
“… 19 Very recently, Galletti et al reported NaIO 4 /TEMPO mediated conversion of benzylamines to carbonyls via imine formation and in situ hydrolysis using H 2 O/CH 3 CN as solvent. 20 However, these methods suffer from limitations such as higher temperature, long reaction time and sequence, substrate selectivity and extra step for imine hydrolysis to form an aldehyde. 17–20 In this context we envisioned that, PhI(OAc) 2 in combination with TEMPO used as an oxidizing agent to convert amine functional groups into corresponding carbonyl compounds at room temperature, with short reaction time and no use of external oxygen source (such as H 2 O or O 2 ) with excellent yields.…”
Section: Introductionmentioning
confidence: 99%
“…The success of benzyl-functionalized substrates but the failure of aliphatic examples lead us to believe that the benzyl group activates the α-carbon of the benzyl amines to undergo hydride transfer and facilitates the process by which the aminium radical cation undergoes hydrogen-atom transfer (HAT) to form the aldimine (Figure ). The lack of success of oxidation in the case of aliphatic substrates is not unprecedented; the oxidation of amines with sodium periodate and TEMPO is not applicable for non-benzylic amines …”
Section: Resultsmentioning
confidence: 99%
“…Amides are ubiquitous in biological systems as well as the motif being found in pharmaceuticals, agrochemicals, and polymers. In addition, transformation of an amide bond can afford an array of synthetically important functionalities including imines, aldehydes, amides, nitriles, and oximes. As a result, simple and effective routes to amides are highly sought after both in academic and industrial settings. The traditional way to synthesize amides involves the coupling of amines with activated carboxylic acids .…”
Section: Introductionmentioning
confidence: 99%
“…69 In 2018, they reported a selective oxidation of amines into their corresponding carbonyl compounds using a TEMPO/NaIO4 catalytic system in an organic-aqueous medium. 70 Bansode and Suryavanshi also reported a similar transformation employing the TEMPO/PhI(OAc)2 system. 71 A pioneering application of this methodology was reported by Kashiwagi et al in 1999.…”
Section: -1 Oxidative Esterification/amidationmentioning
confidence: 89%